LANGUAGE POLITICS IN THE CURRICULUM: A CRITICAL DISCOURSE ANALYSIS OF THE REPRESENTATION OF LOCAL IDENTITY IN INDONESIAN PRIMARY SCHOOL TEXTBOOKS - Yunanto, Fredy (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT This research aims to reveal how representations of local identity are constructed in Indonesian primary school textbooks, as well as to examine the ideological dimensions hidden behind them. Using a critical qualitative approach and Fairclough's Critical Discourse Analysis model, this study analyzes three dimensions: text, discursive practices, and social practices. The study included Indonesian language and Pancasila and Citizenship Education (PPKn) textbooks for grades 4 to 6 of the Merdeka Curriculum edition. The findings show that textbooks consistently shape the discourse of homogeneous nationalism through diction, sentence structure, and metaphors that emphasize unity and a single national identity. Representations of local identities, such as regional figures, regional languages, and local cultural symbols, are minimal and symbolic. The intertextuality between textbooks and national curriculum documents shows the internalization of state ideology in the basic education narrative. Textbook production and distribution practices controlled by central institutions reinforce the homogenization of representations, while the underlying social practices reproduce the central hegemony over regions. These results confirm that textbooks are ideological arenas that play a role in shaping students' awareness of identity, citizenship, and culture. This research recommends the need for reformulation of curriculum policies and textbook production to be more inclusive of local identities, as well as training for writers and educators to be more sensitive to Indonesia's cultural diversity. The CDA approach has proven effective as a tool for criticizing hegemonic educational discourses and opening up space for a more culturally just education. ABSTRAK Penelitian ini bertujuan untuk mengungkap bagaimana representasi identitas lokal dibangun dalam buku teks sekolah dasar Indonesia, serta untuk menganalisis dimensi ideologis yang tersembunyi di baliknya. Dengan menggunakan pendekatan kualitatif kritis dan model Analisis Diskursus Kritis Fairclough, penelitian ini menganalisis tiga dimensi: teks, praktik diskursif, dan praktik sosial. Penelitian ini mencakup buku teks Bahasa Indonesia dan Pendidikan Kewarganegaraan dan Pancasila (PPKn) untuk kelas 4 hingga 6 edisi Kurikulum Merdeka. Hasil penelitian menunjukkan bahwa buku teks secara konsisten membentuk diskursus nasionalisme homogen melalui pilihan kata, struktur kalimat, dan metafora yang menekankan kesatuan dan identitas nasional tunggal. Representasi identitas lokal, seperti tokoh regional, bahasa daerah, dan simbol budaya lokal, minimal dan simbolis. Intertekstualitas antara buku teks dan dokumen kurikulum nasional menunjukkan internalisasi ideologi negara dalam narasi pendidikan dasar. Praktik produksi dan distribusi buku teks yang dikendalikan oleh lembaga pusat memperkuat homogenisasi representasi, sementara praktik sosial yang mendasarinya mempertahankan hegemoni pusat atas daerah. Hasil ini menegaskan bahwa buku teks merupakan arena ideologis yang berperan dalam membentuk kesadaran siswa tentang identitas, kewarganegaraan, dan budaya. Penelitian ini merekomendasikan perlunya reformulasi kebijakan kurikulum dan produksi buku teks agar lebih inklusif terhadap identitas lokal, serta pelatihan bagi penulis dan pendidik untuk lebih sensitif terhadap keragaman budaya Indonesia. Pendekatan CDA telah terbukti efektif sebagai alat untuk mengkritik diskursus pendidikan hegemonik dan membuka ruang untuk pendidikan yang lebih adil secara budaya.